Morphology, structure and enhanced PL of molecular beam epitaxial In0.2Ga0.8As layers on nanopillar patterned GaAs - Riedl, Thomas; Kunnathully, Vinay; Karlisch, A.; Reuter, Dirk; Weber, N.; Meier, Cedrik; Schierholz, R.; Lindner, Jörg

Strain and strain energy in axial-heteroepitaxial GaAs/InAs nanopillars analyzed by atomistic and continuum elastic calculations - Riedl, Thomas; Lindner, Jörg

The influence of the sphere material on the opening size distribution of nanosphere lithography masks - Riedl, Thomas; Lindner, Jörg

Evolution of the opening size of nanosphere lithography masks during thermal annealing - Riedl, Thomas; Kunnathully, Vinay; Lindner, Jörg

Strain Compensation in Single ZnSe/CdSe Quantum Wells: Analytical Model and Experimental Evidence - Rieger, Torsten; Riedl, Thomas; Neumann, Elmar; Grützmacher, Detlev; Lindner, Jörg; Pawlis, Alexander (ACS Applied Materials & Interfaces)

Strain effects on the heteroepitaxy of III-V compound semiconductors on nanopatterned surfaces - Lindner, Jörg; Riedl, Thomas

Ion Beam Modification of Self-Organized Nanostructures - Lindner, Jörg

Bioinspired material design by hierarchical self-assembly on prepatterned surfaces - Brassat, Katharina; Keller, A.; Grundmeier, G.; Bremser, W.; Strube, O.; Lindner, Jörg

Regular surface nanopatterning with nanosphere lithography, block copolymer lithography and cominations of both - Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

Directional Emission from Dielectric Leaky-Wave Nanoantennas - Peter, Manuel; Hildebrandt, Andre; Schlickriede, Christian; Gharib, Kimia; Zentgraf, Thomas; Förstner, Jens; Linden, Stefan (Nano Letters)
Keywords: tet_topic_opticalantenna

Double resonant plasmonic nanoantennas for efficient second harmonic generation in zinc oxide - Weber, Nils; Protte, Maximilian; Walter, Felicitas; Georgi, Philip; Zentgraf, Thomas; Meier, Cedrik (Physical Review B)

Ultrathin Nonlinear Metasurface for Optical Image Encoding - Walter, Felicitas; Li, Guixin; Meier, Cedrik; Zhang, Shuang; Zentgraf, Thomas (Nano Letters)

Identifying and Realizing Symmetries in Quantum Walks - Symmetry Classes and Quantum Walks - Schütte, Philipp

Two-dimensional switchable blue phase gratings manufactured by nanosphere lithography - Wahle, M.; Brassat, Katharina; Ebel, J.; Bürger, Julius; Lindner, Jörg; Kitzerow, Heinz-Siegfried (Optics Express 25)
Switchable two dimensional liquid crystal diffraction gratings are promising can- didates in beam steering devices, multiplexers and holographic displays. For these areas of applications a high degree of integration in optical systems is much sought-after. In the context of diffraction gratings this means that the angle of diffraction should be rather high, which typically poses a problem as the fabrication of small grating periods is challenging. In this paper, we propose the use of nanosphere lithography (NSL) for the fabrication of two-dimensionally structured electrodes with a periodicity of a few micrometers. NSL is based on the self-assembly of micro- or nanometer sized spheres into monolayers. It allows for easy substrate structuring on wafer scale. The manufactured electrode is combined with a liquid crystalline polymer-stabilized blue phase, which facilitates sub-millisecond electrical switching of the diffraction efficiency at adiffractionangle of 21.4°.

Plasmonic nanostructures: spectroscopy and electron microscopy - Kitzerow, Heinz-Siegfried; Lindner, Jörg

Limits of the time-multiplexed photon-counting method - Kruse, Regina; Tiedau, Johannes; Bartley, Tim; Barkhofen, Sonja; Silberhorn, Christine (Physical Review A)

Driven Boson Sampling - Barkhofen, Sonja; Bartley, Tim; Sansoni, Linda; Kruse, Regina; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

High-Efficiency Plug-and-Play Source of Heralded Single Photons - Montaut, Nicola; Sansoni, Linda; Meyer-Scott, Evan; Ricken, Raimund; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)
Keywords: General Physics and Astronomy

Extracting the physical sector of quantum states - Mogilevtsev, D; Teo, Y S; Řeháček, J; Hradil, Z; Tiedau, J; Kruse, R; Harder, G; Silberhorn, Christine; Sanchez-Soto, L L (New Journal of Physics)
Keywords: General Physics and Astronomy

Harnessing temporal modes for multi-photon quantum information processing based on integrated optics - Harder, G.; Ansari, V.; Bartley, Tim; Brecht, Benjamin; Silberhorn, Christine (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences)
In the last few decades, there has been much progress on low loss waveguides, very efficient photon-number detectors and nonlinear processes. Engineered sum-frequency conversion is now at a stage where it allows operation on arbitrary temporal broadband modes, thus making the spectral degree of freedom accessible for information coding. Hereby the information is often encoded into the temporal modes of a single photon. Here, we analyse the prospect of using multi-photon states or squeezed states in different temporal modes based on integrated optics devices. We describe an analogy between mode-selective sum-frequency conversion and a network of spatial beam splitters. Furthermore, we analyse the limits on the achievable squeezing in waveguides with current technology and the loss limits in the conversion process. This article is part of the themed issue ‘Quantum technology for the 21st century’.